Intratumoural aldosterone and CYP11B2 expression levels among different genotypes of aldosterone producing tumours - Tobias Åkerström; Branislav Klimàcek; Matilda Annebäck; Olov Norlén; Peter Stålberg (Endocrine Connections)
Primary aldosteronism is the most common endocrine cause of hypertension, affecting 5–10% of hypertensive patients. Determining the source of aldosteronism is necessary for correct diagnosis and further molecular analysis. To investigate the relationship between aldosterone synthase (CYP11B2) expression and aldosterone synthesis, we analysed tissue aldosterone and CYP11B2 expression in different genotypes of unilateral PA disease (uPA). Forty-eight tumour samples from patients with confirmed uPA were included. Intratumoural aldosterone was detectable in most uPA cases and correlated with CYP11B2 protein expression (r2 = 0.48, P < 0.0001). Aldosterone concentrations were significantly higher in tumours with ATP1A1, ATP2B3 and CACNA1D mutations compared to those with KCNJ5 mutations (P = 0.0001). Using CYP11B2 expression and tissue aldosterone, five tumours were reclassified as non-functional nodules. Furthermore, a second active nodule responsible for the aldosteronism, also carrying a driver mutation, was identified in these patients. These findings show that CYP11B2 expression relates to cell concentrations of aldosterone and may be used to clarify the source of aldosterone secretion. Furthermore, the results corroborate genotype differences between uPA patients.